Randomized trial of a patient empowerment and cognitive training program for older people with diabetes mellitus and cognitive impairment. Issue 12 (1st November 2020) - Wong, Chit‐wai; O, Wai‐Tsun William; Wong, Kin‐Wai Shirley; Ma, Ronald; Hui, Elsie; Kwok, Chi‐yui Timothy
Abstract : Aim: To evaluate the effectiveness of a combined patient empowerment program (PEP) and cognitive training (CT) program on improving glycemic control among older subjects with diabetes and cognitive impairment. Methods: A prospective single blinded, randomized controlled study was carried out in 139 older patients with diabetes aged ≥65 years with memory complaints and recent glycosylated hemoglobin level of 7–9%. They were randomly assigned to either undergo once‐weekly PEP combined with CT for 10 weeks (intervention group, N = 73) or receive no intervention (control group, N = 66). All participants were followed up at months 4 and 12 to examine the immediate and long‐term effects on glycemic control, cognition, mood and compliance to drug and diabetes self‐management. Results: The intervention did not significantly reduce glycosylated hemoglobin. The intervention group showed significant progressive improvement in memory over 1 year and executive function improved significantly at month 12. There was no significant change in diabetes self‐management activities with the intervention. Conclusions: Combination of PEP and CT did not improve glycemic control or self‐care activities in older patients with diabetes and memory complaints but was effective in improving cognitive function in the longer term. Geriatr Gerontol Int 2020; 20: 1164–1170 .